Diagnosis and Surgical Management of Congenital Intranasal Teratoma in a Newborn: A Rare Case Report - W. X. Yeo; K. K. Tan (Case Reports in Otolaryngology)
Teratomas are the most common germ cell tumors of childhood. Head and neck teratomas, however, account for less than five percent of all teratomas. Considered rare at an incidence of 1 in 20,000 to 40,000 live births, they may occur in the cervical region, nasopharynx, brain, orbit, or oropharynx. Teratoma presenting as an isolated intranasal mass is extremely rare. In this report, we describe a case of a mature teratoma arising from the roof of the nasal cavity presenting as an isolated intranasal mass, the first of its kind from our literature review. The tumor was resected endoscopically with no recurrence detected.